Montaigne and the rise of modern cultural diplomacy [version 2; peer review: 2 approved, 1 approved with reservations, 3 not approved] - Gabriel Gherasim (Stosunki Międzynarodowe)
In the troubling sixteenth century political and religious turmoil in Europe - and particularly in France - the cosmopolitan personality of Michel de Montaigne is not only indicative for acknowledging the more and more meddling resources of culture within the realm of politics, but is also explanatory for reforming and expanding the instruments of traditional diplomacy. Specifically, the consequential insights of Montaigne's post-Renaissance humanist stance highly impacted upon certain salient developments in the field of cultural diplomacy that could be analytically framed as i) a personal imprint on reforming political culture(s) tantamount to a conspicuous signature in the field of cultural pedagogy, and ii) a commendable approach to cultural pluralism, and an influential modus operandi in the practice of cultural relations. The present study purports to reflect upon the rise of modern cultural diplomacy through highlighting the impact of the above-mentioned traits on further developments of the field in one of the most characteristic figures of early modernity, Michel de Montaigne.